Severe Anxiety and PTSD Symptoms Among Ebola Virus Disease Survivors and Healthcare Workers in the Context of the COVID-19 Pandemic in Eastern DR Congo - Cénat, Jude Mary; Rousseau, Cécile; Bukaka, Jacqueline; Dalexis, Rose Darly; Guerrier, Mireille (Frontiers in Psychiatry, 2022)
Ebola virus disease (EVD) survivors and healthcare workers (HCWs) face stress, fear, and stigma during the COVID-19 pandemic that can induce severe symptoms of anxiety and post-traumatic stress disorder (PTSD). We examined the prevalence and factors related to severe PTSD and anxiety symptoms, using a representative sample of survivors of the 2018–2020 EVD epidemic in DR Congo in comparison HCWs. Five hundred sixty-three participants (55.25% women, 309 survivors, 202 HCWs, and 52 HCWs and survivors) completed questionnaires assessing anxiety, PTSD, exposure to EVD and COVID-19, stigmatization related to EVD and COVID-19, interpersonal traumas, social support. During the COVID-19 pandemic, 45.6 and 75.0% of survivors and HCWs reported severe symptoms of PTSD and anxiety. Significant difference was observed among the three groups for both PTSD (53.7% survivors, 37.1% HCWs, and 30.8% HCWs-survivors, χ2= 18.67, p < 0.0001) and anxiety (88.3% survivors, 56.9% HCWs, and 65.4% HCWs- survivors, χ2= 67.03, p < 0.0001). Comorbidity of severe PTSD and anxiety symptoms was 42.3% between the three groups. Results revealed that exposure to EVD (b = 0.53; p = 0.001; b = 0.12; p = 0.042), EVD-related stigmatization (b = 0.14; p = 0.018; b = 0.07; p = 0.006), COVID-19-related stigmatization (b = 0.22; p < 0.0001; b = 0.08; p = 0.0001) and social support (b = −0.30; p < 0.0001; b = −0.14; p < 0.0001) predicted severe PTSD and anxiety symptoms. The last models explained 63.8 and 56.4% of the variance of PTSD and anxiety. Symptoms of PTSD and anxiety are common among EVD survivors and HCWs during the COVID-19 pandemic. Culturally-sensitive programs that address stigma are necessary to mitigate the cumulative effects of EVD and the COVID-19 pandemic on EVD survivors and HCWs.